2017
DOI: 10.4103/ijccm.ijccm_459_16
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and outcome of acute kidney injury after congenital heart surgery: A prospective observational study

Abstract: Backgrounds and Aims:Acute kidney injury (AKI) is a frequent event after congenital heart surgery with increased mortality and morbidity. We investigated frequency, risk factors, and associated morbidity and mortality of AKI after pediatric cardiac surgery at a single institution.Methods:Children undergoing congenital heart surgery from March 2013 to February 2016 were assessed for development of AKI based on modified pediatric Risk, Injury, Failure, Loss, and End-stage renal disease criteria. They were also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
(35 reference statements)
0
19
0
2
Order By: Relevance
“…Furthermore, 15 articles were excluded because they did not have the outcome of interest or were duplicate studies. Finally, 30 articles [ 9 – 13 , 26 – 50 ] were selected for the meta-analysis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 15 articles were excluded because they did not have the outcome of interest or were duplicate studies. Finally, 30 articles [ 9 – 13 , 26 – 50 ] were selected for the meta-analysis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Thirty studies [ 9 – 13 , 26 – 50 ] reported the incidence rate of AKI. These studies were significantly heterogeneous ( I 2 = 98.169%, P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The diagnosis of AKI is based on two functional markers, an increase of serum creatinine and a reduction of urinary excretion. Predictors of perioperative AKI in patients undergoing heart surgery include preoperative creatinine level, endstage renal disease, 2-2 phenotype of haptoglobin, advanced age, diabetes mellitus, congestive heart failure, generalized atherosclerosis, cardiovascular collapse, nitric oxide, cyanotic heart disease, duration of surgery and elevated postoperative lactate level [4][5][6][7][8][9]. In patients with severe AKI, oliguria and fluid accumulation, renal replacement therapy is the basic method of treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…KPB ve hipotermi renal kan akımında azalma, hemodilüsyon ve renal tubuler hasara yol açan madde salınımı nedeniyle ABH açısından risk oluşturmaktadır (24) . Bununla beraber, uzamış KPB süresi de ABH gelişimi üzerine ilişkili bulunmuştur (25) . Serimizde de ABH gözlenen grupta, KPB süresinin uzun olması ve hipoterminin düşük olması diğer gruba kıyasla anlamlı fark yaratmış olup, literatürdeki bilgileri desteklemektedir.…”
Section: İstatistiksel Analizunclassified